2021
DOI: 10.3390/pr9020285
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Ion Exchange Resins for Hazardous Ni(II) Removal from Aqueous Solutions: Kinetic and Equilibrium Batch Adsorption Method

Abstract: The development of new, cheaper, and more effective technologies to decrease the amount of wastewater containing heavy metals and to improve the quality is indispensable. Adsorption has become one of the alternative treatment methods. A small number of studies focusing on the batch technique for nickel ion removal by the new generation ion exchangers are described in the literature. In this paper, the Ni(II) removal from aqueous solutions using the ion exchange resins of different types was investigated. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 65 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…An increase in the anionic forms of heavy metals in the solution increases the adsorption ability on the anion exchange resin; therefore, the removal efficiency is the highest for Zn(II) (fraction of anionic zinc chloro-complexes is higher compared to copper(II) ones) but in the concentrated HCl solution the competition effect can be responsible for the slight removal of efficiency reduction [ 72 ]. The mechanism of heavy metal ions adsorption onto the anion exchanger can be described as ion-exchange, which is illustrated in [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the anionic forms of heavy metals in the solution increases the adsorption ability on the anion exchange resin; therefore, the removal efficiency is the highest for Zn(II) (fraction of anionic zinc chloro-complexes is higher compared to copper(II) ones) but in the concentrated HCl solution the competition effect can be responsible for the slight removal of efficiency reduction [ 72 ]. The mechanism of heavy metal ions adsorption onto the anion exchanger can be described as ion-exchange, which is illustrated in [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cu(II), Ni(II), Co(II), Zn(II), Pb(II) ions were effectively removed by the strongly (Lewatit MonoPlus M500, Lewatit MonoPlus MP 500 [ 45 ], Amberlite IRA458, Amberlite IRA958 [ 46 , 47 ], Amberlite IRA 402 [ 47 ], Amberlite IRA402 [ 48 ]) and weakly basic (Amberlite IRA67 [ 46 ]) anion exchange resins in the presence of various complexing agents. Our previous studies concerning Co(II), Ni(II), Cu(II) and Zn(II) removal on the weakly (Purolite A830, Lewatit MonoPlusTP220), intermediate (Amberlite IRA478RF) and strongly (Dowex MSA1, Dowex MSA2, Lewatit MonoPlus SR7, Purolite A400TL) basic anion exchangers, as well as the chelating (Purolite S984) and carbon-based (Lewatit AF5) adsorbent showed that the highest capacity was obtained for the resin of bis-picolyamine functional groups [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, precipitation [ 6 , 7 ], membrane process [ 8 , 9 ], ion exchange [ 10 , 11 ] and adsorption [ 12 , 13 ] techniques have been demonstrated to effectively eliminate heavy metal ions from contaminated water. Among them, adsorption is a promising and effective method for practical use due to its high efficiency, simple design and easy operation [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium was achieved within a small contact time (8 min) due to the availability of the unoccupied adsorbent's surface area, thus qualifying a faster adsorption rate. Furthermore, the high removal efficiencies may also be attributed to the adsorption mechanism and possible ion exchange occurrence [52]. The homogenous and heterogenous surface presence of Na-zeolite P 1 was evidenced by equilibrium data obeying the Langmuir and Freundlich models.…”
Section: Zeolitesmentioning
confidence: 97%